Nuit et brouillard - Resnais, Alain (France, 1955)
Hailed as one of the world's greatest documentaries, "Night and Fog" is the definitive film on Nazi concentration camps and a devastating record of man's inhumanity to man. Like a master conductor, director Alain Resnais (Hiroshima, Mon Amour, Last Year at Marienbad) weaves contemporary images of the abandoned camp at Auschwitz with newsreel footage of the atrocities that occurred there. Juxtaposing color and black-and-white film, "Night and Fog" brings the horror of the Holocaust to the present. An elegy on memory and immeasurable sorrow, this tightly structured half-hour film foreshadows Resnais' remarkable feature films. Upon its release, Francois Truffaut called it the greatest film ever made.
Duration: 00:30:00
Keywords: Documentary films